Analisis Penggunaan QRIS sebagai Media Transaksi Digital Pedagang Kaki Lima di Daerah Jakarta Barat - Yosep Hendri Gumilang; Shihabudin; Sri Redjeki; Nurhayati Pratiwi; Findita Ratna Kusumaningrum (STIT Sirojul Falah Bogor, 2025)
This study aims to analyze the use of Quick Response Code Indonesian Standard (QRIS) as a digital transaction medium among street vendors in West Jakarta. Using a qualitative approach through in-depth interviews with four street vendors in one area in West Jakarta, this study explores the reasons for adoption, benefits, challenges, and impact of QRIS on turnover and customer trust. The results show that QRIS was adopted to cater to urban customers' preference for cashless payments, improve transaction efficiency, security, and financial record keeping, and attract more customers. However, merchants face constraints such as internet connection interruptions, fraud risks, QR Code validity period, and administrative costs. QRIS knowledge is gained from informal sources, with minimal formal training. Customers responded positively, although some older customers still preferred cash. QRIS increases turnover and customer trust, while merchants expect a more secure system, stable internet, lower administration costs, and more training.